Conforming to accreditation in Iranian hospitals. Issue 2 (June 2016) - Agrizzi, Dila; Agyemang, Gloria; Jaafaripooyan, Ebrahim
Abstract: This paper examines the operation of an accreditation programme for hospitals in Iran. It explores the process of accreditation as a regulatory control system and analyses hospitals' responses to this type of control. We draw on the notion of steering and argue that the accreditation system is transactional in nature. Our findings show that hospitals conform to the scheme, although they also resist some of its requirements. On a wider policy level, we suggest that accreditations offer the accreditor the opportunity to impact on how activities are undertaken, but hospitals require incentives in order to make the necessary organisational changes.